Burnout and Ways of Preventing It: A Qualitative Analysis - Michalak, Sylwia; Olejnik, Iwona (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2023)
Objective: The aim of our study is to identify ways of counteracting burnout by employers, and employers’ support for workers affected by burnout as indicated by young people setting out in their professional careers.Research Design & Methods: The framework was developed with the use of qualitative methodology. Focus group interviews (FGI) were used as the research method. The study was conducted in Poland among five groups.Findings: Young people are aware of burnout and its effects. They can propose several ways to prevent burnout on their own, but they acknowledge that they may be insufficient to fully cope with the problem, particularly if they operate in an environment conducive to burnout, or where the employer does not take active measures to prevent burnout.Implications / Recommendations: Burnout is a real threat to humans and causes numerous problems for enterprises. The article contains recommendations regarding the expectations young people have of employers and their support for employees affected by burnout.Contribution: The study contributes to and expands the knowledge about burnout in education and professional contexts and organisational prevention methods from the perspective of young people.